(untitled) (CIPEEX, 2022)
CARDIAC AMYLOIDOSIS IS A MULTISYSTEM PATHOLOGY, RARE AND STILL UNDERDIAGNOSED, ESPECIALLY WHEN RELATED TO TRANSTHYRETIN. IN CLINICAL PRACTICE, AMYLOID DEPOSITS IN CARDIAC TISSUE ARE USUALLY FOUND IN THE ELDERLY AND THE PRESENTATION OF THIS DISEASE IS USUALLY VARIABLE AND CAN BE CONFUSED WITH OTHER PATHOLOGIES. THEREFORE, THE PRESENT CASE REPORT AIMS TO DESCRIBE THE CONDITION OF AN ELDERLY PATIENT DIAGNOSED WITH TRANSTHYRETIN-ACQUIRED CARDIAC AMYLOIDOSIS (ATTR), HAVING IMPORTANT CARDIAC REPERCUSSIONS AND WORSENING THE PATIENT’S PROGNOSIS. THE DIAGNOSIS WAS BASED ON THE OBSERVATION OF THE NT-PROBNP MARKER, A PREDICTOR OF HEART FAILURE AND CARDIAC AMYLOIDOSIS, AND ON IMAGING TESTS, SCINTIGRAPHY WITH RADIOTRACERS, MAGNETIC RESONANCE IMAGING AND ECHOCARDIOGRAPHY. MALE PATIENT, 88 YEARS OLD, CONSULTED WITH A CARDIOLOGIST IN 2019 AFTER REFERRAL BY A GERIATRICIAN, COMPLAINING OF DYSPNEA. ONLY IN 2020, THE SCINTIGRAPHIC EXAMINATION WITH RADIOTRACERS CONFIRMED THE DIAGNOSTIC HYPOTHESIS OF ATTR AND THERAPEUTIC PLANS WERE ESTABLISHED, MAINLY RELATED TO THE DRUG TAFAMIDIS - STABILIZER OF THE FIBRINOID MATERIAL. THESE PROCEDURES LED TO AN INCREASE IN THE PATIENT’S QUALITY OF LIFE AND ATTENUATION OF THE RISK OF DEATH.